Impaired induction of interleukin 28B and expression of interferon λ 4 associated with nonresponse to interferon‐based therapy in chronic hepatitis C. Issue 6 (June 2015) - Murakawa, Miyako; Asahina, Yasuhiro; Nakagawa, Mina; Sakamoto, Naoya; Nitta, Sayuri; Kusano‐Kitazume, Akiko; Watanabe, Takako; Kawai‐Kitahata, Fukiko; Otani, Satoshi; Taniguchi, Miki; Goto, Fumio; Nishimura‐Sakurai, Yuki; et al.
Abstract Background and Aim Interferon (IFN) λ plays an important role in innate immunity to protect against hepatitis C viral (HCV) infection. Single nucleotide polymorphisms (SNPs) near IL28B (IFNλ3) are strongly associated with treatment response to IFNα therapy in chronic hepatitis C (CHC) patients. Recently, IFNλ4 related to IL28B‐unfavorable allele was discovered. However, the impact of IFNλs on CHC is unknown. We aimed to investigate the mechanism underlying responsiveness to IFN‐based therapy in CHC associated with SNPs near IL28B. Methods We evaluated the basal mRNA levels and ex‐vivo induction of IFNλ expression including IFNλ4 in peripheral blood mononuclear cells (PBMCs) from 50 CHC patients treated with pegylated‐IFNα/RBV. Furthermore, we investigated the effect of IFNλ4 on induction of IL28B in vitro. Results When PBMCs were stimulated with IFNα and polyinosinic–polycytidylic acid, IL28B induction was significantly lower in patients with IL28B‐unfavorable genotype (rs12979860 CT/TT) than those with IL28B‐favorable genotype (rs12979860 CC; P = 0.049). IL28B induction was lower in nonresponders than in relapsers (P = 0.04), and it was also lower in nonsustained virological responder patients for triple therapy including NS3 protease inhibitors. IFNλ4 mRNA was detected in 12 of 26 patients with IL28B‐unfavorable SNP, and IFNλ4 expression was associated with lower IL28B induction in patients with IL28B‐unfavorable genotype (P = 0.04) and nonresponse to IFNα therapy (P = 0.003). Overexpression of IFNλ4 suppressed IL28B induction and promoter activation. Conclusions Impaired induction of IL28B, related to IFNλ4 expression in PBMCs of IL28B‐unfavorable patients, is associated with nonresponse to IFNα‐based therapy for hepatitis C viral infection.